1998
DOI: 10.1021/bi9814944
|View full text |Cite
|
Sign up to set email alerts
|

The Family 1 β-Glucosidases from Pyrococcus furiosus and Agrobacterium faecalis Share a Common Catalytic Mechanism

Abstract: Comparisons of catalytic mechanisms have not previously been performed for homologous enzymes from hyperthermophilic and mesophilic sources. Here, the beta-glucosidase from the hyperthermophilic archaeon Pyrococcus furiosus was recombinantly produced in Escherichia coli and shown to have biophyscial and biochemical properties identical to those of the wild-type enzyme. Moreover, the recombinant enzyme was subjected to a detailed kinetic investigation at 95 degreesC to compare its catalytic mechanism to that de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
45
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 57 publications
15
45
0
Order By: Relevance
“…Kinetic parameters for ChiB cat on pNp-chitooligosaccharides and chitooligosaccharides are summarized in Table 1. For the pNp-linked substrates studied, the highest k cat /K m was observed for pNpchitotetraose, and the highest catalytic efficiency (k cat /K m ) was noted on (GlcNAc) 4 and (GlcNAc) 5 for the series of chitooligosaccharides. Initial rates of chitooligosaccharide hydrolysis showed that the enzyme exhibited Michaelis-Menten kinetics with a DP of Ն3, although significant substrate inhibition was noted on oligosaccharides with a DP of 4 to 6 at concentrations of Ն0.8 mM (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Kinetic parameters for ChiB cat on pNp-chitooligosaccharides and chitooligosaccharides are summarized in Table 1. For the pNp-linked substrates studied, the highest k cat /K m was observed for pNpchitotetraose, and the highest catalytic efficiency (k cat /K m ) was noted on (GlcNAc) 4 and (GlcNAc) 5 for the series of chitooligosaccharides. Initial rates of chitooligosaccharide hydrolysis showed that the enzyme exhibited Michaelis-Menten kinetics with a DP of Ն3, although significant substrate inhibition was noted on oligosaccharides with a DP of 4 to 6 at concentrations of Ն0.8 mM (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Although this chitinase is not closely related to ChiB cat , the specific activity and turnover numbers (k cat ) of ChiB cat are 2 orders of magnitude higher than for the mesophilic organism. Both enzymes showed similar substrate specificity (k cat /K m ) on (GlcNAc) 5 and (GlcNAc) 6 . However, ChiB cat exhibited an order of magnitude higher specific activity on (GlcNAc) 4 than the V. furnissii endochitinase ( Table 1), indicating that a tetrasaccharide optimally binds to the active site of ChiB cat .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Otherwise, hyperthermophilic and mesophilic enzymes are highly similar: (i) the sequences of homologous hyperthermophilic and mesophilic proteins are typically 40 to 85% similar (79,350); (ii) their three-dimensional structures are superposable (16,63,143,160,227,284,327); and (iii) they have the same catalytic mechanisms (22,350,386).…”
Section: Hyperthermophilic Proteins Are Highly Similar To Their Mesopmentioning
confidence: 99%
“…The synergistic activities of several of these enzymes may be needed to degrade polysaccharides in vitro. In combination, ␤-glucosidase (Cel1) (4,30), laminarinase (Lam16) (24), and endoglucanase (Cel13) (2) from P. furiosus rapidly hydrolyze barley ␤-glucan to smaller oligosaccharides and ultimately glucose (15). Because two endo-acting glycosidases appear to be secreted by P. furiosus, as shown by the presence of putative signal peptides, and the ␤-glucosidase is cytoplasmic, an oligosaccharide transport system must also be involved in the utilization of barley ␤-glucan as a carbon and energy source.…”
mentioning
confidence: 99%